Implementasi Algoritma MFCC dan KNN dalam Identifikasi Nada Dasar Alat Musik Kendang (Informatics Department, Faculty of Mathematics and Natural Sciences, Udayana University, 2023)
Balinese kendang is a Balinese musical instrument that is closely related to the art of karawitan. Usually drums are played in a musical instrument show in Bali. Balinese drums are played in pairs, which consist of lanang drums and wadon drums. The sound features used in this system are extracted from the MFCC algorithm which are then classified using the KNN algorithm. The results of the system show the best classification results with an accuracy of 90% with parameter K = 1 and can correctly recognize 54 tones out of 60 tones.